Characteristics of Open Coal Mine Wastewater Conditions in Tanah Bumbu District, South Kalimantan, Indonesia - SUJIMAN, Sujiman (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research aims to determine the condition of waste in terms of the quality of the elements Fe, Mn, pH and TSS, and to determine the tendency of this waste in the settling pond of coal mines in Tanah Bumbu Regency, South Kalimantan.               The research results show that at the settling pond location of the open coal mine the concentration of Fe quality is between (0.023 – 6.50) mg/lt and Mn (0.02-2.14) mg/lt, and the TSS quality is 76 mg/lt to 801 mg/lt and the pH is between 6.40 to 8.10. Trends in Fe waste Most of the results are still below environmental quality standards, only in July 2022 the quality will increase to 6.5 mg/lt. Meanwhile, Mn waste for a year is still below the government's standard environmental quality standards, but the highest quality is in September 2024 reaching 3.35 mg/lt, this quality is still below environmental quality standards. The trend in pH quality in general is still normal, only in February 2024 the quality exceeds environmental quality standards, increasing to 8.10 mg/lt. Finally, for TSS quality, the trend is from January to August 2024 to decrease, then in September it increases significantly to 801 mg/lt and then gradually decreases until December 2024 to 182 mg/lt. Keywords : Environmental quality standards, Coal mine wastewater, trends quality.